TEACHING THE CHARACTER OF NATIONALISM IN HISTORICAL MATERIALS IN ELEMENTARY SCHOOLS - Nur Fitri; Wahdan Najib Habiby (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Nationalism is the noble value of Pancasila which must be owned by students as the next generation of the nation to realize their independence and contribution to the country, so that the competitive character of students can be realized among themselves in the era of globalization. This study aims to reduce the content of the characters and their teaching methods in the class IV package book theme 5 of the 2018 Revised Edition of My Hero Curriculum 2013. This type of research is descriptive qualitative research with content analysis, namely research that describes the Character of Nationalism and is then used to analyze the contents of teacher and class student books. 4 themes 5 My heroes. The results of the research and discussion that the researchers conducted showed that 1) The content of the character of nationalism in student books still contained some material that did not meet predetermined indicators, namely the